Sequential Adaptation in Mammalian CHO-K1 Cells Producing Human Erythropoietin - Wisnuwardhani, Popi Hadi; Septisetyani, Endah Puji; Santoso, Adi (ANNALES BOGORIENSES, 2017)
The production of recombinant proteins for clinical applications using mammalian cell technology has become a prevalent system because of its capacity in assembling functional proteins. One of the main problems with CHO-K1 cells is that this cell has to grow in the presence of serum. However, the presence of serum will complicate the downstream step for protein production. Thus, protein produced in media without serum, theoretically, would be easier to purify. Technically, this type of cell can be produced by growing the CHO-K1 cells in serum-free media by using adaptation method in suspension condition. This research showed that through sequential adaptation using conditioned media, the CHO-K1 cell line that produces the human erythropoietin gene (hEPO) was able to grow in suspension culture using serum-free media. Based on Western blot analysis, it showed that the protein (hEPO) was able to be expressed in suspension culture with molecular mass of about 47 kDa.